Analisis Likuiditas, Solvabilitas dan Profitabilitas kinerja perusahaan di PT. Asia Sejahtera Mina TB - Rida latifah, Rida Latifah; Nazwa Norsa’adah, Nazwa Norsa’adah; Isra Misra , Isra Misra (Opportunity Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This article discusses the influence of liquidity, solvency, and profitability on the company's performance in PT. Asia Sejahtera Mina TBK. This study aims to analyze how these three variables contribute to the company's financial performance. The method used is multiple regression analysis with data taken from the company's financial statements for the last five years. The results of the study show that liquidity has a positive and significant influence on the company's performance, while solvency shows a varied influence. Profitability has also proven to contribute significantly to improving the company's performance. This finding provides insight for company management in making strategic decisions to improve the financial performance and competitiveness of PT. Asia Sejahtera Mina Tbk in the market.